Kryopreservasi Sebagai Upaya Konservasi Plasma Nutfah Jangka Panjang Secara in Vitro Beberapa Genotipe Pisang (Musa Spp L.) - Wiwik Hardaningsih (Jurnal Embrio, 2012)
Research on long-term conservation of germplasm various banana genotypes (Musa spp L.) with kryopreservasi in liquid nitrogen (-196oC temperature) has been conducted at the Laboratory of Tissue Culture and Germplasm Conservation ITFRI Solok. This study aims to: know the method of conservation of banana germplasm with long-term conservation kryopreservasi suitable for a variety of banana genotypes. The results showed that: kryopreservasi method that can used for long term storage is a method of slow freezing (slow cooling cryopreservation) by using the vitrification method given the addition of PVS2 cryoprotectant atthawing temperatures 40oC.